Representasi Nilai Budaya Bugis dalam Novel Athirah Karya Alberthiene Endah: Kaman Etnografi - Siti Hasriyati; Arisa; Sutrisman; Hj. Andi Ebe; Putri Wulandari (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstract: Representation of Bugis Cultural Values ​​in the Novel Athirah by Alberthiene Endah: Kaman Ethnography. This study aims to represent bugis cultural values in Athirah's novel. This type of research is qualitatid research. The object of research analyzed is the value of Bugis culture in the novel Athirah by Alberthiene Endah. The data described are Bugis cultural values using aspects of social values and religious values. The source of data in this study is the novel Athirah by Alberthiene Endah. Data collection techniques are analytical techniques using the method of recording, observing, and determining novel texts. The results of this study are (1) the form of social values in bugis cultural culture includes five things, namely, caring for family, caring for others, being honest, independent, and polite. (2) the form of religious values in Bugis culture includes three things, namely, akidah, worship, and morals. The form of conveying bugis cultural values in the novel Athirah by Alberthiene Endah is a form of attitude and behavior of the character in his life.